Answers

  • Brainly User
2015-12-16T21:38:50+08:00
The equation does not represent a circle because the radius ≤ 0. 

x² + y² + 13 = 4x + 6y
x² - 4x + y² - 6y + 13 = 0
x² - 4x - (4/2)² + y² - 6y - (6/2)² = -13
x² - 4x + y² - 6y - 4 - 9 = -13
x² - 4x + y² - 6y - 13 = - 13
x² - 4x + y² - 6y = -13 + 13
x² - 4x + y² - 6y = 0

or:
(x-2)² + (y-3)² = -13



0
Oops, sorry it should be x squared + y squared -4x-6y+4+9+13 = 0 or x squared + y squared -4x-6y=-26 in general form Ax squared + By squared + Cx + Dy + E = 0.  Still, the equation does not represent circle.